A Study of the Relationship between CA 19-9 Level and Infection with H. pylori in Patients with Benign Gastrointestinal Diseases - عوامة, محمد; مخلوف, سامر; كرميا, زين العابدين (Latakia University Journal -Medical Sciences Series, 2021)
Helicobacter pylori infection is now recognized as a worldwide problem and that is because it is the most common cause of chronic gastritis, and has been strongly linked to peptic ulcer disease and gastric cancer. This study aims to study the relationship between levels of the cancer marker CA 19-9 and Helicobacter pylori infection in patients with benign gastrointestinal diseases visiting the Internal Gastroenterology Clinic at Tishreen University Hospital. The study sample included 81 patients who underwent an upper gastrointestinal endoscopy with the aim of investigating the cause of digestive complaints. Digestive complaints ranged from obstinate epigastric pain, nausea and vomiting. Then, tissue biopsies were taken to detect the presence of H. pylori. The study found that there was no statistically significant relationship between age, sex, and the type of disease diagnosed with histopathology on the one hand and the incidence of H. pylori on the other hand. The study also concluded that there is no relationship between infection with H. pylori and serological CA 19-9 levels.